Effect of calcination temperature on the silica ceramic membrane synthesized via sol-gel dip-coating method - Mohd Daud, Farah Diana; Kahlib, Nor Amyra Zulianey; Mohd Rafi, Muhammad Husaini; Mel, Maizirwan; Ahmad Azhar, Ahmad Zahirani; Hassan, Noor Azlina; Nor Hairin, Assayidatul Laila (UR Publishers, 2018)
Ceramic membranes became one of the most important ceramic products because of their numerous benefits to many applications especially in gas separation processes. The attractive features offered by this technology include high energy efficiency, simplicity design and construction of membrane modules and environmental compatibility. The aim of this project is to get the optimum calcination temperature thus will give the optimize pore size for separation gas without cracking or pinholes the membranes. Therefore, the silica ceramic membrane was fabricated via sol-gel dip-coating method and the effect of calcination temperature on the membrane pore size was investigated. The ceramic support was dipped in the mixture solution of tetraethyl orthosilicate (TEOS), distilled water, ethyl alcohol and nitric acid with the desired molar ratio followed up by the calcination process at 400 °C, 500 °C and 600 °C. For X-ray diffraction (XRD) results, the fabricated silica ceramic membrane shows the existence of silicate hydrate when calcined at 400 °C, 500 °C and 600 °C. The XRD analysis showed the highest peak intensity at 22.5° which proved the presence of silica. From the field emission electron microscopy (FESEM) images, the pore size of the ceramic support was around 0.5 to 0.6 μm. After the silica ceramic membranes were fabricated, the pore size no longer visible under the FESEM proves that the pore size of the membranes was reduced. Fourier transform infrared spectroscopy (FTIR) showed adsorption spectra of the fabricated membranes with different calcination temperature. The broad band in the region around 1060 to 1090 cm-1 correspond to the O-Si-O bond of mesoporous silica altogether confirming the existence of silica. Based on the result analysis, the suitable calcination temperature at 500 °C with less crack and more consolidated surface membrane.